Spatial and nonlinear effects of local government debt on environmental pollution: Evidence from China - Li, Feifei; Huang, Jieyu; Du, Mingyue (Frontiers in Environmental Science, 2022)
As an important means for the government to dispatch social funds, debt issuance acts a key role in the government's implementation of environmental supervision and governance policies. Based on the panel data of 30 provinces in China from 2011 to 2019, this paper utilizes spatial econometric model and threshold panel model to investigate the influence of local government debt on environmental pollution. The empirical results indicate that both environmental pollution and local government debt have significant positive spatial agglomeration effect, that is, the provinces with poor environmental quality have higher environmental pollution levels in their neighboring provinces, and the provinces with large local government debts will also have spillover effects on the surrounding provinces. The influence of local government debt on environmental pollution is non-linear, and the non-linear relationship between them still holds after considering the spatial effect. Specifically, the government debt’s influence on environmental pollution shows a U-shaped feature of first restraining and then promoting, and the single threshold effect model confirms this conclusion. The analysis of regional heterogeneity suggests that in the eastern region, local government debt’s influence on environmental pollution is always restraining, while in the central and western regions, this influence keep in line with the national level, showing a U-shaped feature. The research results of this paper enrich the related literature on the consequences of local government debt, and provide empirical evidence for China to scientifically formulate debt prevention and control measures from an environmental perspective.